The Effect of Ginger on Pregnancy-Induced Nausea during First Trimester - Navabeh Hosseinkhani; Tahereh Sadeghi (Iran University of Medical Sciences, 2009)
Background and Aim: Pregnancy-induced nausea significantly reduces women's quality of life making considerable distress. Ginger is already being used in traditional folk medicine to treat nausea and vomiting in populations. The aim of the study was to determine the effect of ginger on pregnancy-induced nausea during the first trimester of the pregnancy.   Material and method: This was a double blind randomized placebo trial with control group in which 121 pregnant women referred to antenatal clinic at or before 17 weeks gestation and suffered from nausea was randomly allocated to either experimental, placebo, or control group. The severity of nausea was recorded by visual analog scale 24 hours before intervention and during 4 consecutive days after intervention. Data were analyzed by nonparametric and parametric tests.   Results : The findings showed that the nausea severity was statistically different in ginger group before and after treatment (at first, second third and fourth days) (P≤0.001). The same was true for placebo group (P<0.05), but, not for control group.   The findings also showed that ginger was more effective on decreasing the severity of nausea (P<0/05) than the placebo and control groups.   Conclusion : Oral ginger is effective on decreasing the severity of nausea during the first trimester of pregnancy and the drug have a positive mental effect on pregnant mothers, leading to decrease the severity of nausea.